Randomized controlled trial of antenatal magnesium sulfate for short-term neuroprotection in premature neonates - C, Manoj Varanattu; Menon, Bindu; Sankar, Ajay; M, Anand; Manikoth, Prakash (Indian Journal of Child Health, 2022)
Objective: To test the hypothesis that antenatal magnesium sulfate (MgSO4) has a short term neuroprotective role in the early neonatal period, when given to women considered at risk for preterm delivery in a developing country. Study Design: Randomized, placebo-controlled, open label, trial. Participants: A total of 126 mothers who delivered at or below 34 weeks gestation were randomized to receive either antenatal MgSO4 (cases) or normal saline as placebo (controls). A total of 108 babies born were observed for the primary and secondary outcomes. Primary Outcome: The composite of the incidence of death and intraventricular hemorrhage (IVH) by cranial ultrasonography in surviving preterm infants. Results: There were 6 deaths in cases and 11 deaths in controls (relative risk [RR]: 0.54; 95% confidence interval [CI]: 0.2173-1.369; p=0.18). A statistically significant reduction in the number of IVH was observed in cases (n=1) compared to controls (n=9) (RR: 0.11; 95% CI: 0.0145-0.897; p=0.016) with a number needed to treat of 7. Conclusion: Antenatal MgSO4 resulted in a significant reduction in the risk of IVH in preterm infants born at or below 34 weeks of gestation.